RESPONCE OF CORN GRAIN TRAITS TO HARVESTING MOISTURE - & Baktash, Al-kazaali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted during spring and fall seasons, 2015, at the fields of Field Crop Department– College of Agriculture– University of Baghdad. The objective was to evaluate response of corn synthetic variety 5018 traits in next generation  to harvesting moisture in the first generation. In spring season 2015, seeds of the synthetic variety 5018 were planted. When moisture of the ear grains was reached the first treatment (37-42%), ten ears were harvested. Ears harvesting dates were performed manually when the grains had 37-42%, 34-36%, 30-33%, 25- 28% and 19-22% moisture content. In fall season 2015, varietal trail was carried out to the five treatment materials, using Randomized Complete Bock Design, with four replicates. The results showed, significant differences among treatments for all the studied traits, except grain filling duration. The highest grain growth rate (7.23 mg.grain.day-1) and grain yield (159.46 g.plant-1), were produced from plants grown it's seeds harvested with (19-22)%, which didn't differ significantly from the plants grown it's seeds  harvested with moisture (25-28)%. It can be conclude that the perfect corn grain moisture for harvesting (19-22)% for the nex generation seeds .